(3TQM gjGcd GdfhQs - (3LdGd GdOjf eMeO Hf CSYO GdLOhGfj GdUOjbjs; (3Gb TeS GdOjf , eMeO Hf CMeO Hf eMeO Hf TgGH GdOjf GdSgQhQOjs
(3ChdgG (B:s
(3agPG CjgG GdPcj GdeJhbO TQM dgjGcd GdfhQ HEHQGR ecfhfGJ CSQGQg s
(3BNQgG (B:s
(3HeG jdjb HESJYOGO cd aQO hGddg fYe NjQ ef CYGf aj JMUjd GdeWGdH Je GdcJGH GdTQja s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJUha hGdBOGH GdTQYjIs